Automated Signal Quality Assessment for Heart Sound Signal by Novel Features and Evaluation in Open Public Datasets. (24th February 2021) - Tang, Hong; Wang, Miao; Hu, Yating; Guo, Binbin; Li, Ting
Abstract : Automated heart sound signal quality assessment is a necessary step for reliable analysis of heart sound signal. An unavoidable processing step for this objective is the heart sound segmentation, which is still a challenging task from a technical viewpoint. In this study, ten features are defined to evaluate the quality of heart sound signal without segmentation. The ten features come from kurtosis, energy ratio, frequency-smoothed envelope, and degree of sound periodicity, where five of them are novel in signal quality assessment. We have collected a total of 7893 recordings from open public heart sound databases and performed manual annotation for each recording as gold standard quality label. The signal quality is classified based on two schemes: binary classification ("unacceptable" and "acceptable") and triple classification ("unacceptable", "good, " and "excellent"). Sequential forward feature selection shows that the feature "the degree of periodicity" gives an accuracy rate of 73.1% in binary SVM classification. The top five features dominate the classification performance and give an accuracy rate of 92%. The binary classifier has excellent generalization ability since the accuracy rate reaches to (90.4 ± 0.5 ) % even if 10% of the data is used to train the classifier. The rate increases to (94.3 ± 0.7 ) % in 10-fold validation. The triple classification has an accuracy rate of (85.7 ± 0.6 ) % in 10-fold validation. The results verify the effectiveness of the signal quality assessment, which could serve as a potential candidate as a preprocessing in future automatic heart sound analysis in clinical application.